Tvet and career development - Hayward, Geoff (Nazarbayev University Graduate School of Education, 2015)
There is now general agreement that high quality primary education is a key component of economic success in a globalizing knowledge economy. High quality general secondary education also seems essential for economic growth in the modern world. Developing young people’s abilities to play with ideas and information seems to be crucial to technological innovation and imitation of technological innovation.
Keywords: tvet; career development; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education